(untitled) (Journal of Ideas in Health, 2025)
Background: Myxobolus species are Myxosporean parasites affecting various fish, causing diseases that weaken populations and result in substantial economic losses in aquaculture and fisheries. Despite extensive studies in Asia, Europe, and the Americas, there is limited research on Myxobolus in Africa, particularly in Tanzania, where fisheries and aquaculture are vital for fish populations, ecosystem health, and economic growth. Methods: This study investigated the prevalence and genetic characteristics of Myxobolus parasites in 384 fish samples from Dar es Salaam (Indian Ocean) and Mwanza (Lake Victoria). Samples were examined for cysts and spores using microscopy, followed by molecular characterization through PCR amplification of the 18S rDNA gene, Sanger sequencing, phylogenetic analysis, and genetic distance evaluation. Results: The overall prevalence of Myxobolus was 12%, with a significantly higher prevalence in Mwanza (21.88%) compared to Dar es Salaam (2.08%). Statistical analysis revealed significant associations between prevalence, fish species, and locality. Phylogenetic analysis identified two genetic lineages within a monophyletic group, clustering with Myxobolus species from Israel, Egypt, and Ghana, suggesting potential novel species. Genetic distance analysis indicated greater variation in saltwater samples compared to freshwater. Conclusion: These findings highlight the higher prevalence of Myxobolus in freshwater and emphasize the need for targeted management strategies, continued surveillance, and research to safeguard fish populations and sustain aquaculture.